2023
DOI: 10.1186/s12874-023-01845-4
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate longitudinal data for survival analysis of cardiovascular event prediction in young adults: insights from a comparative explainable study

Abstract: Background Multivariate longitudinal data are under-utilized for survival analysis compared to cross-sectional data (CS - data collected once across cohort). Particularly in cardiovascular risk prediction, despite available methods of longitudinal data analysis, the value of longitudinal information has not been established in terms of improved predictive accuracy and clinical applicability. Methods We investigated the value of longitudinal data ov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…As a benchmark, we also fit static survival models at three time points (5 years, 15 years, and 25 years after baseline) to compare with the dynamic survival models. ( 18 ) The idea is similar to landmarking approaches, in which a survival model is fit to the subjects who are still at risk at the landmarking time. For consistency in comparison, we used Dynamic-DeepHit and made an artificial cut-off at the landmarking time (meaning, covariate measurements after Y5, Y15, and Y25 were excluded from the static model at landmarking time 5 years, 15 years, and 25 years after baseline, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…As a benchmark, we also fit static survival models at three time points (5 years, 15 years, and 25 years after baseline) to compare with the dynamic survival models. ( 18 ) The idea is similar to landmarking approaches, in which a survival model is fit to the subjects who are still at risk at the landmarking time. For consistency in comparison, we used Dynamic-DeepHit and made an artificial cut-off at the landmarking time (meaning, covariate measurements after Y5, Y15, and Y25 were excluded from the static model at landmarking time 5 years, 15 years, and 25 years after baseline, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…16,17 As a benchmark, we also fit static survival models at three time points (5 years, 15 years, and 25 years after baseline) to compare with the dynamic survival models. 18 The idea is similar to landmarking approaches, in which a survival model is fit to the subjects who are still at risk at the landmarking time. For consistency in comparison, we used Dynamic-DeepHit and made an artificial cut-off at the landmarking time (meaning, covariate measurements after Y5, Y15, and Y25 were excluded from the static model at landmarking time 5 years, 15 years, and 25 years after baseline, respectively).…”
Section: Modeling Methodsmentioning
confidence: 99%
“…A study of publications from 2009 to 2016 revealed that less than 8% of predictive models included longitudinal data as time‐varying covariates. 6 Neglecting the potential of these high‐dimensional, longitudinal, time‐varying covariates to improve prediction, as demonstrated in cardiovascular disease risk prediction, 7 , 8 is a prevailing issue.…”
Section: Introductionmentioning
confidence: 99%